2012
DOI: 10.1002/anie.201108502
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Mediated CI Bond Activation of Iodobenzene

Abstract: Controversy resolved! A combination of gas-phase ion-molecule reactions and theoretical studies confirm bisligated mononuclear Au(I) complexes are unable to undergo oxidative addition of iodobenzene for Sonogashira coupling, but that the ligated gold clusters [Au(3)L(n)](+) (L=Ph(2)P(CH(2))(n)PPh(2); n=3-6) activate the C-I bond. DFT calculations on the transition states show that the linker size n tunes the cluster reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 40 publications
(24 reference statements)
1
53
0
2
Order By: Relevance
“…Interestingly, coordination of both phosphine donor arms lowers the activation barrier for the CBr bond cleavage significantly, in contrast to the usual observed reluctance of (bis)phosphine gold(I) complexes to undergo oxidative addition (vide supra) [66].…”
Section: Oxidative Addition Of Aryl Halides To Gold(i)mentioning
confidence: 75%
See 1 more Smart Citation
“…Interestingly, coordination of both phosphine donor arms lowers the activation barrier for the CBr bond cleavage significantly, in contrast to the usual observed reluctance of (bis)phosphine gold(I) complexes to undergo oxidative addition (vide supra) [66].…”
Section: Oxidative Addition Of Aryl Halides To Gold(i)mentioning
confidence: 75%
“…In the course of this controversy concerning the ability of gold(I) complexes to undergo oxidative addition of aryl halides, O'Hair and coworkers [66] investigated the reaction of iodobenzene with gold(I) complexes and small gold clusters by means of mass spectrometry and DFT-computations. While cationic bis(phosphine) gold(I) complexes proved to be inert towards iodobenzene, the monoligated cationic phosphine complexes were shown to undergo C-I activation reactions: iodobenzene and trimethylphosphine or triphenylphosphine gold(I) complexes formed adducts, as indicated by detection of the corresponding cations in the gas phase.…”
Section: Oxidative Addition Of Aryl Halides To Gold(i)mentioning
confidence: 99%
“…[16] Using a bis-ligated cationic gold complex 8, they did not observe any product resulting from oxidative addition by mass spectrometry (1). Calculations confirmed that this reaction was endothermic and had a high activation energy.…”
Section: Methodsmentioning
confidence: 99%
“…IMRs within a mass spectrometer can easily rule out such impurities by mass selecting the catalyst of interest. So, in 2012 O'Hair and coworkers studied the gas-phase reactivity of iodobenzene with the mononuclear gold(I) complex [Au(PPh 3 ) 2 ] + and ligated gold clusters [Au 3 L n ] + where L n = Ph 2 P(CH 2 ) n PPh 2 (Scheme 2) [31]. Kinetic analysis of the gas-phase reactions with iodobenzene (Table 1) showed that while the bis-ligated mononuclear gold(I) was inactive with respect to oxidative addition, the ligated gold clusters were active.…”
Section: Oxidative Additionmentioning
confidence: 99%